Carlos Astrada: Martín Heidegger. Editor Juárez. Buenos Aires, 1970. 372 p. - Pró, Diego F. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía Argentina y Americana, 1972)

(untitled)
Fil: Pró, Diego F..